(untitled) (Journal of the College of Basic Education, 2022)
The educational researchers felt the importance of modern teaching methods that focus on students and through which the achievement of many educational and educational goals, and since the increase of students’ achievement and tendency towards science is one of the main goals in teaching science, and showed many teaching models, including Perkins and Blith. The purpose of the research is to identify the model (Perkins and Plaith) in the collection and the tendency towards science for middle-class students by verifying the following zero hypotheses: There is no statistically significant difference at the level of significance (0.05) between the average student scores of the experimental group that studied the science subject according to the model (Perkins and Belith) the average of the class of the officer who studied the science subject according to the usual method of collection. There is no statistically significant difference at the level of significance (0.05) between the average scores of students of the experimental group that studied science according to the Perkins and Belith) the average grade of the officer group that studied science in accordance with the usual method is the measure of inclination towards science. The current search determines: Students of the first grade intermediate - secondary Al-Adnanieh for girls. Second semester of the school year (2016-2017). The Third Unit: Genetics and Evolution: The First and Second Classes of the Science Book of the Mediterranean Class, Second Edition, Ministry of Education Press, Baghdad, 2016 The research sample of (60) students from the first average student was randomly distributed to two groups evenly, the first (30) students studied according to the module (Perkins and Blithe) and a female officer (30) who studied in the usual way. The two groups were paralleled in the variables (intelligence - previous student achievement - previous information). The researcher prepared a collection test of (20) paragraphs, and adopted a ready measure for the scale of inclination towards the science. The results showed the superiority of the experimental group on the control group. In light of this , the researcher developed a number of suggestions and recommendation.